TEACHING ENGLISH THROUGH “SUGGESTOPEDIA” - Shermamatova, Zaynab Azimjonovna; Bozorova , Marjona Bakhtiyorovna; Olimjonov , Ibrohim Soyibjonovich (Educational Research in Universal Sciences, 2023)
In the 1960s, psychologist George Lozanov proposed the suggestion teaching approach, which offers a fresh perspective on the evolution of English reading instruction. Positive recommendations can put people’s bodies in a relaxed state and their minds in an active state. Suggestive media highlights the fact that individuals are suggestive. This healthy mental and physical state can help students reach their maximum potential and increase the effectiveness of their foreign language acquisition. The use of Suggestopedia in English language instruction is examined in this article. Recommended tactics are presented by Suggestopedia, including double communication, a calm and intuitive setting, and positive unconscious cues. It was discovered that the recommended teaching strategy has certain issues. The recommended teaching approach includes strict guidelines.